2023
DOI: 10.3389/fendo.2023.1068254
|View full text |Cite
|
Sign up to set email alerts
|

Effects of E-health-based interventions on glycemic control for patients with type 2 diabetes: a Bayesian network meta-analysis

Abstract: The high disease burden of type 2 diabetes seriously affects the quality of life of patients, and with the deep integration of the Internet and healthcare, the application of electronic tools and information technology to has become a trend for disease management. The aim of this study was to evaluate the effectiveness of different forms and durations of E-health interventions in achieving glycemic control in type 2 diabetes patients. PubMed, Embase, Cochrane, and Clinical Trials.gov were searched for randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Therefore, a further reduction in HbA1c would be expected if the system was extended to the entire follow-up. A recent meta-analysis in which E-health interventions including SMS, smartphone applications and phone calls were compared showed that SMS was a lower-cost and lower-barrier technology in achieving the best effect in reducing HbA1c, with an optimal duration of ≤ 6 months [31].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a further reduction in HbA1c would be expected if the system was extended to the entire follow-up. A recent meta-analysis in which E-health interventions including SMS, smartphone applications and phone calls were compared showed that SMS was a lower-cost and lower-barrier technology in achieving the best effect in reducing HbA1c, with an optimal duration of ≤ 6 months [31].…”
Section: Discussionmentioning
confidence: 99%
“…E-health interventions were required to be designed with the goal of enhancing PA. E-health interventions refer to any interventions that incorporate at least one of the following components: smartphone apps, wearable activity trackers, websites, phone calls, video consultation, and electronic messages (e.g., text messages, social media messages, email) (Peng et al 2022 ; Zhang et al 2023 ). Both single and multi-modal e-health interventions were included.…”
Section: Methodsmentioning
confidence: 99%
“…[31][32][33] The release of a study in May 2023 proves that this study considers the most recent research. 34 Nevertheless, it is essential to note that before this publication, the research protocol was designed, and funding was obtained in 2022 to start the study. This study offers two advantages: first, a subgroup analysis is included to examine how COVID-19 has affected telemedicine interventions, emphasising T2DM management.…”
Section: Open Accessmentioning
confidence: 99%